Determinants and outcomes of prolonged anxiety and depression in idiopathic pulmonary fibrosis. Issue 2 (17th August 2017) - Glaspole, Ian N.; Watson, Alice L.; Allan, Heather; Chapman, Sally; Cooper, Wendy A.; Corte, Tamera J.; Ellis, Samantha; Grainge, Christopher; Goh, Nicole; Hopkins, Peter; Keir, Gregory; Macansh, Sacha; et al.
We have recently shown that anxiety and depression are common comorbidities for people with interstitial lung disease (ILD). In a cross-sectional single-centre study, the prevalence of anxiety was 31% and the prevalence of depression was 23% [1]. Anxiety and depression were not related to physiological parameters; however, dyspnoea and number of comorbidities were important contributors. The aims of this study were to determine the frequency of prolonged anxiety and depression among sufferers of idiopathic pulmonary fibrosis (IPF), and factors contributing to their persistence. Prolonged anxiety and depression occur frequently in IPF and strongly relate to dyspnoea and cough http://ow.ly/iWxV30cLCfl